Chronological dynamics of the gut microbiome in response to the pasture grazing system in geese - Qasim Ali; Sen Ma; Umar Farooq; Boshuai Liu; Zhichang Wang; Hao Sun; Yalei Cui; Defeng Li; Yinghua Shi (Microbiology Spectrum, 2024)
ABSTRACT It is commonly accepted that dietary fibers are good for gut health. The effect of fibers on the diversity and metabolic activities of the cecal microflora, however, differ with the passage of time. Therefore, we investigated the time-series impacts of the pasture grazing system (a high dietary fiber source) on the cecal microbiome and short-chain fatty acids in Wanpu geese, comparing it to commercial feeding (a low dietary fiber source). The cecal microbiota composition and SCFA concentrations were evaluated by 16S rRNA gene sequencing and gas chromatography, respectively. We found that pasture produced a generally quick positive response to Bacteroidales, Lactobacillales, Gastranaerophilales (at 45 days), Lachnospirales, and Oscillospirales (at 60 days and 90 days) irrespective of Erysipelotrichales (at 45 days), Clostridia_UCG-014, RF39 (at 60 days), Christensenellales, and Peptostreptococcales-Tissierellales (at 90 days) in geese. Meanwhile, we found that Lactobacillales, Gastranaerophilales, Lachnospirales, and Oscillospirales were significantly correlated with short-chain fatty acids in pasture grazing geese. Indeed, the correlation of cecal microbiota with SCFAs led to altered microbial functions evinced by COG; KEGG pathway levels 1, 2, and 3; BugBase; and FAPROTAX databases. This study emphasizes the importance of dietary fiber sources in influencing beneficial impacts in regulating geese microbiota homeostasis and metabolic functions such as energy and lipid metabolism.IMPORTANCELow dietary fiber diet sources cause gut microbial and short-chain fatty acid alterations that lead to compromised animal health. The establishment of an artificial pasture grazing system at the expense of ryegrass is a good source of dietary fiber for geese. Our results described the importance of pasture in maintaining the gut microbiota, SCFAs, and potential microbial functions reported by COG; KEGG pathway levels 1, 2, and 3; BugBase; and FAPROTAX databases.